2022
DOI: 10.1007/s11033-022-07245-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in GJB2, COL4A3, ATP6V1B1 and EDNRB variants detected among hearing impaired families in Morocco

Abstract: Deafness has a very variable disease. It may occur as a result of external auditory canal involvement or a de ciency in the sound conduction mechanism (transmission deafness) or impairment of the cochlear, cochlear nerve or central auditory perception. Genetics is the most common cause, as approximately 70% of hearing disorders are of hereditary origin. 1/3 of hereditary deafness is syndromic (associated with other symptoms) and 2/3 are non-syndromic (isolated deafness). At this date, 173 loci of deafness gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results of this study revealed the presence of a rare dominant variant p.R184Q in one family. This variant was reported in the literature in several patients with autosomal dominant nonsyndromic HL, including a Moroccan family, in whom it was recently identified by whole-exome sequencing [35‒38]. p.R184Q causes arginine-to-glutamine replacement at the highly conserved 184th position.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed the presence of a rare dominant variant p.R184Q in one family. This variant was reported in the literature in several patients with autosomal dominant nonsyndromic HL, including a Moroccan family, in whom it was recently identified by whole-exome sequencing [35‒38]. p.R184Q causes arginine-to-glutamine replacement at the highly conserved 184th position.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous and homozygous mutations in EDNRB and ET-3 are found in patients of Waardenburg-Shah syndrome (WS-IV) that is one kind of syndromes with genetic hearing loss (GHL) ( Huang et al, 2021 ). Homozygous mutations of the EDNRB gene can be also identified in Moroccan deaf patients ( AitRaise et al, 2022 ).…”
Section: Roles Of Class a G Protein-coupled Receptors In Cochleamentioning
confidence: 99%